Strategi Manajemen dan Supervisi Pendidikan dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam: (Sebuah Systematic Literature Review) - Ilpa Hasanah; Abdur Rahim Lubis; Darwis Darwis; Kasman Kasman4 (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
This study aims to evaluate the quality of Islamic Religious Education (PAI) learning as an indicator of educational success because it produces students with strong academic, spiritual, and character competencies. However, several issues, such as teachers lacking adequate pedagogical competencies, poor learning management, and ineffective academic supervision, remain challenges to improving the quality of PAI learning. Data were obtained from national scientific articles published between 2020 and 2025 and related to the research topic. The results indicate that systematic learning planning, continuous teacher competency development, the use of educational technology, strengthening the leadership of school or madrasah principals, and collaborative academic supervision improve the quality of PAI learning. Academic supervision has also been shown to improve teacher competency through coaching, mentoring, and evaluation. These results confirm that collaboration between academic supervision and educational management is crucial for achieving quality PAI learning.